PENERAPAN SISTEM E-KATALOG SEBAGAI POLA KEMITRAAN UNTUK MENINGKATKAN PRODUKTIVITAS UMKM: Studi Pada Kemitraan Batu Orange Cake dan Bagian Pengadaan Barang dan Jasa Kota Batu - Dwi Sofian, Octa (JOURNAL AKSES STIA MALANG, 2024)
This research aims to determine the application of the e-catalog system implemented by the Batu City Goods and Services Procurement Section, especially in the process of procuring goods and services within the Batu City Government. Apart from that, to analyze more deeply about a partnership process, especially for UMKM in Batu City, related to the existence of an e-catalog. By implementing the e-catalog, it provides space for movement in partnerships between government agencies and UMKM in Batu City. The problem focuses on the partnership process which includes: use of digital technology, transparency of UMKM, dependence on government and administrative requirements. This research refers to the implementation of an e-catalog system related to the partnership process with UMKM. The research method used is descriptive qualitative by analyzing human resource development strategies. Data was collected through interviews with staff in the Batu City Goods and Services Procurement Section as well as the head of Batu Orange Cake UMKM. This study concludes that the partnership has been implemented and needs to be improved at certain points during the partnership process.